Nowhere safe? Exploring the influence of urbanization across mainland and insular seashores in continental Portugal and the Azorean Archipelago. Issue 2 (30th January 2017) - Bertocci, Iacopo; Arenas, Francisco; Cacabelos, Eva; Martins, Gustavo M.; Seabra, Maria I.; Álvaro, Nuno V.; Fernandes, Joana N.; Gaião, Raquel; Mamede, Nuno; Mulas, Martina; Neto, Ana I.
Abstract: Differences in the structure and functioning of intensively urbanized vs. less human-affected systems are reported, but such evidence is available for a much larger extent in terrestrial than in marine systems. We examined the hypotheses that (i) urbanization was associated to different patterns of variation of intertidal assemblages between urban and extra-urban environments; (ii) such patterns were consistent across mainland and insular systems, spatial scales from 10s cm to 100s km, and a three months period. Several trends emerged: (i) a more homogeneous distribution of most algal groups in the urban compared to the extra-urban condition and the opposite pattern of most invertebrates; (ii) smaller/larger variances of most organisms where these were, respectively, less/more abundant; (iii) largest variability of most response variables at small scale; (iv) no facilitation of invasive species by urbanization and larger cover of canopy-forming algae in the insular extra-urban condition. Present findings confirm the acknowledged notion that future management strategies will require to include representative assemblages and their relevant scales of variation associated to urbanization gradients on both the mainland and the islands. Highlights: Coastal assemblages compared between urban vs. extra-urban locations at mainland and insular systems Most algal groups distributed more homogeneously in the urban condition Most invertebrates distributed more homogeneously in the extra-urban condition Smallest (tens centimetres) scale as the most relevant for intertidal organisms Invaders not facilitated by urbanization, algal canopies occurring only in the insular extra-urban condition